Sense of Place, Physical Activity, and Quality of Life as a Part of Community Well-being in Three European Community - Hossein Mousazadeh (Department of Urban and Regional Planning, Diponegoro University, 2022)
The present study considers the measurement of quality of life as indicators of community well-being, which can be affected by the conditions of physical health, psychological, environment, and relationships of community residents. The purpose of this study was to test the perception of the residents of the community about the effect of the river and the satisfaction of the residents in different areas of life. This research was tested using a survey of 450 respondents from different communities in Europe. Participants completed measures of the World Health Organization Quality of Life-BREF questionnaire, Sense of place questionnaire, and author survey questionnaire about the type of Physical Activity. The results highlighted that all five domains of quality of life are strongly related to the length of time living by the river. Most of the participants stated that living by the river increases their self-confidence, security, and spirit of participation, which is directly related to enhancing the well-being and quality of life of citizens. According to the findings, the factor of security by the river is the most frequent. Participants who had lived near a river for more than 15 years were more likely to report greater physical activity, sense of place, and thus quality of life. In addition, several socio-demographic and basic factors related to the quality of life of the participants were also identified in this research.